2007
DOI: 10.1002/macp.200700161
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Formation of Amorphous Gold Nanoparticles within Spherical Polyelectrolyte Brushes

Abstract: We present a comprehensive investigation on the formation of gold nanoparticles in spherical polyelectrolyte brushes. These colloidal carrier particles consist of a solid polystyrene core onto which long cationic polyelectrolyte chains are grafted. Immersed in water these polyelectrolyte chains can be used to enrich AuCl ions. The metal ions thus confined in the polyelectrolyte layer can be reduced to gold nanoparticles of approximately 1 nm diameter. Cryogenic transmission electron microscopy shows that the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(48 citation statements)
references
References 34 publications
5
43
0
Order By: Relevance
“…Figure 4 plots the activation energy results as well as the TOF of the catalysts. As can be seen, the activation energy results for the catalysts are within the range previously reported for metallic catalysts (7.5 kJ/mol -110 kJ/mol) [11,14,[39][40][41][42]. The monometallic Au NPs had an activation energy of 12.7 kJ/mol.…”
Section: Arrhenius Equation Analysissupporting
confidence: 85%
“…Figure 4 plots the activation energy results as well as the TOF of the catalysts. As can be seen, the activation energy results for the catalysts are within the range previously reported for metallic catalysts (7.5 kJ/mol -110 kJ/mol) [11,14,[39][40][41][42]. The monometallic Au NPs had an activation energy of 12.7 kJ/mol.…”
Section: Arrhenius Equation Analysissupporting
confidence: 85%
“…Wunder et al [63] reported an E A of 40 kJ·mol -1 for the normalized rate constant of Pt NPs immobilized onto a cationic spherical polyelectrolyte brush. Th is was in good agreement with their previous work using the same carrier system for metal NPs, where the E A was found to be 44 kJ·mol -1 [60,61,92]. Th ey demonstrated that the E A refl ects the temperature dependence of the kinetic constant k app and of the two thermodynamic adsorption constants K 4-NP and K BH 4 -.…”
Section: Temperature and Activation Energysupporting
confidence: 80%
“…Schrinner et al (2007) investigated the mechanism of formation of highly stable amorphous GNPs of about 1 nm diameter in presence of cationic polyelectrolyte brushes carrying chains of poly(2-aminoethyl methacrylate hydrochloride). They ascribed the excellent stability of GNPs to a strong attraction between negatively charged GNPs and positively charged polyelectrolyte chains.…”
Section: Introductionmentioning
confidence: 99%